Localized Electrons Enhanced Ion Transport for Ultrafast Electrochemical Energy Storage. Issue 14 (26th February 2020) - Chen, Jiewei; Luo, Bi; Chen, Qiushui; Li, Fei; Guo, Yanjiao; Wu, Tom; Peng, Peng; Qin, Xian; Wu, Gaoxiang; Cui, Mengqi; Liu, Lehao; Chu, Lihua; et al.
Abstract: The rate‐determining process for electrochemical energy storage is largely determined by ion transport occurring in the electrode materials. Apart from decreasing the distance of ion diffusion, the enhancement of ionic mobility is crucial for ion transport. Here, a localized electron enhanced ion transport mechanism to promote ion mobility for ultrafast energy storage is proposed. Theoretical calculations and analysis reveal that highly localized electrons can be induced by intrinsic defects, and the migration barrier of ions can be obviously reduced. Consistently, experiment results reveal that this mechanism leads to an enhancement of Li/Na ion diffusivity by two orders of magnitude. At high mass loading of 10 mg cm −2 and high rate of 10C, a reversible energy storage capacity up to 190 mAh g −1 is achieved, which is ten times greater than achievable by commercial crystals with comparable dimensions. Abstract : Fast ion transport inside an electrode material is crucial to efficient electrochemical energy storage. Based on the localized electrons enhanced ion‐transport mechanism, Li/Na‐ion diffusivity can be enhanced by two orders of magnitude after introducing abundant localized electrons. Meanwhile, the corresponding prepared ion‐batteries can show ten times enhanced capacity than commercial crystals at high mass loading and high rate.